QJava: setas quânticas em Java - Calegaro, Bruno Crestani (2013)
Quantum computing is an emerging technology that, currently, has the challenge of developing programming languages, according to the rules of quantum mechanics, to support the creation, analysis, modeling and simulation of high-level quantum algorithms. Particularly, the focus is on the investigation of new semantic models to develop programming languages for quantum computing. In this context, one alternative is to use the semantic model of monads and arrows that abstracts both pure and mixed quantum states and also can express measures. This model however, was originally implemented as a library for the functional language Haskell, which not every programmer is family. This way, this study aims to provide a universal tool for high-level quantum programming, providing a library for Java. This library was implemented using the new features of closures present in the version 8 of the JDK (Java Development Kit), already available in developers preview. In addition, we present a specific syntax for the library to facilitate the development of quantum algorithms with a clearly structured notation. This syntax is described in a notation similar to the do-notation of Haskell and operates in conjunction with a parser implemented by ANTLR tool.